EVALUATION OF PERIAPICAL HEALING USING CBCT: A CASE SERIES - Mihaela Salceanu; Cristi Giuroiu; Claudiu Topoliceanu; Doriana Agop-Forna; Yllka Decoli; Cristina Antohi; Tudor Hamburda; Anca Melian (Romanian Society of Oral Rehabilitation, 2021)
The aim of this study is to investigate the possibilities of diagnosis and post-treatment monitoring of chronic periapical lesions. Materials and method. Five cases of chronic periapical lesions in various stages of evolution located in the posterior dental group, were exposed and described. Patients were included in the treatment within the Clinical Education Base "M. Kogălniceanu" of the Faculty of Dentistry, U.M.F. "Grigore T.Popa" Iaşi. All patients were treated using mechanical and chemical treatment followed by application of Ca (OH) 2 paste for a period of 14 days. Root closure was performed by cold lateral condensation associated with Endoflas sealant (Sanlor, Columbia). Coronary restorations were performed with Ketac Molar glassionomer cement (3M / ESPE) and Filtek250 composite resin (3M / ESPE). CBCT images (pretreatment, 3 months posttreatment) were obtained using PaX-Uni3D (TVAPANO04, VATECH) and the dimensions of periapical lesions in coronal-apical, mesial-distal and buccal-oral sections were measured using the Ez3D 2009 Plus software application. CBCT parameters were set for 20 second exposure time, 85 kV, 5mA. The mean values ​​of the CBCT-PAI index pre-treatment and at 3 months post-treatment were recorded. Results. All investigated cases showed a reduction in CBCT-PAI indices at 3 months post-treatment following the healing processes of periapical pathology. Conclusion. CBCT examination and CBCT-PAI index are precise, reliable and reproducible tools in the evaluation of the post-treatment evolution of the chronic periapical lesions.